2003
DOI: 10.1002/app.12353
|View full text |Cite
|
Sign up to set email alerts
|

Polyglycolide‐based blends for drug delivery: A differential scanning calorimetry study of the melting behavior

Abstract: ABSTRACT:The melting behavior of polyglycolide (PGA) with eight other biodegradable polymers was investigated to determine whether forming a blend could be used as a method of lowering the melting point of PGA. Blends were prepared by melt processing in differential scanning calorimetry (DSC) pans and were then analyzed by DSC. In every case, a comparison of the blend DSC plot with those of the two individual components showed that the melting behavior of PGA remained unchanged by blending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A weak interaction between high molecular weight polymers can be thermodynamically unfavorable. This would promote the formation of lower stability co‐crystals and result in decreased crystallinity . In addition, the crystallinity of the PGC copolymer also decreased, as is evident from the Δ H f of PGC (35.6 J g −1 ) and that for 2:1 PCL/PGC (5.65 J g −1 ) due to blending with PCL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A weak interaction between high molecular weight polymers can be thermodynamically unfavorable. This would promote the formation of lower stability co‐crystals and result in decreased crystallinity . In addition, the crystallinity of the PGC copolymer also decreased, as is evident from the Δ H f of PGC (35.6 J g −1 ) and that for 2:1 PCL/PGC (5.65 J g −1 ) due to blending with PCL.…”
Section: Resultsmentioning
confidence: 99%
“…This would promote the formation of lower stability co-crystals and result in decreased crystallinity. 37 In addition, the crystallinity of the PGC copolymer also decreased, as is evident from the ΔH f of PGC (35.6 J g −1 ) and that for 2:1 PCL/PGC (5.65 J g −1 ) due to blending with PCL. Overall, PCL/PGC blends exhibited lower crystallinity than the respective pure polymers.…”
Section: Structural Morphological and Thermal Propertiesmentioning
confidence: 93%
“…This has been shown experimentally in several studies involving blends in which one or both components were polyesters. In particular, Dickers et al investigated blends of PGA with PCL, poly( d, l ‐lactide), and poly(3‐hydroxybutyrateco‐3‐hydroxyvalerate) (PHBHV) 23, 24…”
Section: Introductionmentioning
confidence: 99%
“…Incredible choices in the polymeric designs offer a direct route to optimal carrier design. Different types of implantable devices have been used, such as non-biodegradable silastic tubes which have encountered issues with their removal after the end of treatment [8]; use of poly(lactide-co-glycolide) (PLGA)-based implants which have shown development of fibrous encapsulation around the implant site [9]; and use of high melting-point polymers which limit their application to compounds with high thermal stability [10]. We recently reported that biodegradable polycaprolactone:F68 implants embedded with chemopreventive agents provided sustained release for long duration in vivo [6; 11].…”
Section: Introductionmentioning
confidence: 99%